The Research Trend of Statistical Significance Test: Bibliometric Analysis - Al Husaeni, Dwi Fitria; Al Husaeni, Dwi Novia; Fiandini, Meli; Nandiyanto, Asep Bayu Dani (ASEAN Journal of Educational Research and Technology, 2024)
A significance test is a test that can determine whether a research hypothesis is accepted or not. Therefore, significance tests need to be carried out, especially for researchers who will conduct research related to hypothesis testing. This research discusses publication trends regarding significance tests. This research aims to analyze research trends regarding statistical significance tests using bibliometric analysis methods assisted by mapping analysis. Bibliometric analysis methods and mapping analysis with VOSviewer were used in this research. The data source was taken from the Google Scholar database in the period 2013 - 2023. The total number of documents found during the last 10 years was 1000 documents. Based on the research results, it was found that the number of publications regarding statistical significance tests has decreased every year. From a total of 281 documents in 2013 to 7 documents in 2023. The results of article data mapping produce three forms of visualization, namely network, overlay, and density visualization. The mapping results show that research on statistics still needs to be carried out, especially regarding significance tests. This research concluded that the trend of research discussing statistical significance tests is decreasing, although, in terms of its use, it is still very important, especially in processing quantitative research data.